Effect Of Muscle Energy Technique On Craniovertebral And Shoulder Angles In Forward Head Posture (Journal of Pharmaceutical Negative Results, 2023)
Purpose The aim of this study was to investigate the effect of muscle energy technique in craniovertebral angle and shoulder angle in subjects with forward head posture. Methods Overall, 60 participants of both genders (45 males and 15 females) with forward head posture (FHP) aged 18 - 23 years and Body Mass Index (BMI) range 18 -25 kg/m² were randomly assigned to 2 groups (A and B). Group A (n=30) received muscle energy technique in addition to conventional strengthening and stretching exercises and postural advices 3 times per week for 4-weeks. Group B (n=30) received conventional strengthening and stretching exercises and postural advices 3 times per week for 4-weeks. To assess craniovertebral angle (CVA) and Shoulder angle (SA), Photographic Posture Analysis was used. Pain intensity was evaluated with Visual analogue scale (VAS) scores, and A pressure pain algometer served to measure the pain pressure threshold (PPT). All subjects’ outcomes were assessed before and after treatment. For statistical analysis, t-test was conducted to investigate the effect of treatment. Results A statistically significant effect (p < 0.0001) of treatment and time was revealed in both groups for all measured variables. Between-group analysis implied a higher improvement in post-intervention results in group A (p < 0.05). Conclusion This study indicated improvement in both groups, but adding Muscle energy technique to conventional therapy resulted in more improvement in all measured variables.